Compact high power laser source. - Abas @ Ismail, Ahmad Fauzi; Husham, Husham Kadhum (2011)
A high power laser source for generating an output beam with a stable wavelength includes a laser diode comprising a gain medium, a pump source for providing light to the gain medium and at optical resonator. The laser source further includes a guide means comprising at least one reflector, and a fiber grating for stabilizing the wavelength of the output beam. The laser diode is coupled to the fiber grating via the guide means in a compact packaging arrangement.